KNEKS and the Dynamics of Sharia Economic Law Bureaucratization in Indonesia (2016–Present) - Iskandar, Iskandar; Addiarrahman, Addiarrahman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article examines the bureaucratization dynamics of sharia economic law through the role of the National Committee for Islamic Economy and Finance (KNEKS). Employing a qualitative research design with an institutional–legal analysis approach, the study draws on documentary analysis, official policy documents, and in-depth interviews with key informants. The findings demonstrate that, in contrast to the Indonesian Council of Ulama (MUI), which functions as a quasi-legislative body producing normative legal instruments, KNEKS operates primarily as a legal structure that coordinates and harmonizes cross-institutional policies within the sharia economic governance framework. However, the study also reveals a persistent gap between legal structure and legal culture, as KNEKS’s institutional positioning has yet to significantly enhance public legal awareness and literacy in sharia economic law. This article contributes to the literature on Islamic legal governance by offering an institutional perspective on bureaucratization processes and highlighting the need for policy formulations that integrate bureaucratic mechanisms with community-based social capital to strengthen legal culture in sharia economic development